2014
DOI: 10.1016/j.amjoto.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in Human Papillomavirus (HPV) associated head and neck cancer

Abstract: Purpose Poorer survival from head and neck squamous cell carcinoma (HNSCC) in African Americans (AA) may be due to disparity in the prevalence of Human Papillomavirus (HPV) but earlier studies often failed to control other etiological factors. We aimed to elucidate whether racial disparities in HPV prevalence and overall survival were due to confounding from smoking or alcohol use. Materials and Methods 385 patients with SCC of the mouth, pharynx, nose, or larynx who had surgical resection at Wayne State Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 35 publications
2
45
0
Order By: Relevance
“…The study's large sample spans 14 years and includes cases from all regions of the US, allowing for a comprehensive assessment of primary anatomical sites, clinical factors, and temporal trends in HNSCCs among nH black and white males. Our results expand on both previous studies using SEER data (Shiboski et al 2007), which do not adequately reflect geographic diversity (Data 18-Mar-2009), and on smaller localized studies (Gourin and Podolsky 2006;Jiron et al 2014;Zandberg et al 2014), which do not allow for evaluation of temporal trends in HNSCCs or for comprehensive analyses of primary anatomical sites.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The study's large sample spans 14 years and includes cases from all regions of the US, allowing for a comprehensive assessment of primary anatomical sites, clinical factors, and temporal trends in HNSCCs among nH black and white males. Our results expand on both previous studies using SEER data (Shiboski et al 2007), which do not adequately reflect geographic diversity (Data 18-Mar-2009), and on smaller localized studies (Gourin and Podolsky 2006;Jiron et al 2014;Zandberg et al 2014), which do not allow for evaluation of temporal trends in HNSCCs or for comprehensive analyses of primary anatomical sites.…”
Section: Discussionsupporting
confidence: 60%
“…Similar to findings across study populations (Betiol et al 2013;Chaturvedi et al 2008;Ryerson et al 2008), the majority of HPV types within NCDB were type 16 or types 16/18 combined. Studies have shown a higher incidence of HPV-related HNSCCs in nH whites than in nH blacks (Jiron et al 2014;Settle et al 2009;Zandberg et al 2015), and the majority of HPV-related cases within our study were among nH whites. Our analysis of a subset of cases from 2004 to 2012 demonstrated a higher incidence of HPV-related tumors among nH white males in oropharyngeal and non-oropharyngeal site groups, in local and distant stages, and across all grade categories, except for well-differentiated tumors.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…We also previously observed and reported a racial survival disparity between black and white patients in OPSCC in an independent patient population in a multicenter TAX-324 chemo-and radiotherapy trial [11]. In that study, there was no racial difference in survival in non-oropharyngeal sites; the more favorable overall survival in white patients with OPSCC was driven by increased prevalence of [38]. In contrast, Weinberger et al and Isayeva et al noticed no significant racial HPV prevalence between blacks and whites in their studies, but racial differences in survival could be accounted for by pairing HPV and p16 co-results [30,39].…”
Section: Discussionmentioning
confidence: 75%
“…3 The so-called HPV epidemic is most prominent in patients of Northern European and North American origin, whereas other areas of the world still see few HPVassociated tumors. [4][5][6] In studies that include an assessment of HPV status, a shift in the traditional risk factors is nearly universally noted: viral-associated tumors are seen in younger populations that have lymph node-positive oropharyngeal carcinomas and lower rates of smoking. 7 Having said this, most patients with HPV-associated oropharyngeal carcinoma are still men in their 50s who have a smoking history, and true nonsmokers constitute only a minority.…”
Section: Introductionmentioning
confidence: 99%